Computer-aided Analysis of Selective Phytochemicals as Potent Inhibitors of Parkin: Major Biological Target of Parkinson's disease - Nadia Arif; Andleeb Subhani; Waqar Hussain; Nouman Rasool (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2020)
Parkinson's disease, caused by mutations in the Parkin that leads to loss of neuron is the second most widespread neurodegenerative disorder in the world. Phytochemicals are being considered due to their medicinal properties to cure many human diseases. The present study targets the inhibition of Parkin, a major biological target for Parkinson using 3150 phytochemicals from various medicinal plants. These plants are naturally growing in a local climate of Pakistan, India and China and being used for a long time for the medicinal purpose. A total of 3150 phytochemicals from various medicinal plants were collected for this in silico study. The pharmacological assessments prediction, molecular docking and density functional theory (DFT) based studies were done to find out the latent inhibitory properties of these phytochemicals against Parkin. Out of 3150 phytochemicals, 175 showed human-suitable pharmacological properties and among those 175 compounds, 5 phytochemicals, i.e. Liquirtin, Shinflavanone, Glabrone, GlycyrdioneB and IsoangustoneA to have potent inhibitory properties against Parkin and can be deliberated for additional in vitro and in vivo studies to evaluate their inhibitory effects against Parkin. They revealed binding affinity greater than various previously reported inhibitors against Parkin. Additionally, DFT based analysis exhibited high reactivity for these five phytochemicals in the binding pocket of Parkin, based on ELUMO, EHOMO and band energy gap. A total of 5 out of 175 phytochemicals are reported as highly potent inhibitors against Parkin which are liquirtin, Shinflavanone, Glabrone, Glycyrdione B and IsoangustoneA from the same medicinal plant Glycyrrhiza glabra. However, these 5 phytochemicals can be considered for further in vivo and in vitro analysis for the clinical development of a drug against the world's second most common brain disorder, the Parkinson's disease.